1996
DOI: 10.1111/j.1469-7610.1996.tb01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Executive Functions and Developmental Psychopathology

Abstract: In this paper, we consider the domain of executive functions (EFs) and their possible role in developmental psychopathologies. We first consider general theoretical and measurement issues involved in studying EFs and then review studies of EFs in four developmental psychopathologies: attention deficit hyperactivity disorder (ADHD), conduct disorder (CD), autism, and Tourette syndrome (TS). Our review reveals that EF deficits are consistently found in both ADHD and autism but not in CD (without ADHD) or in TS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

85
1,953
8
81

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,618 publications
(2,127 citation statements)
references
References 224 publications
85
1,953
8
81
Order By: Relevance
“…Using young rats with neonatal 6-hydroxydopamine lesions as a model for ADHD, we reported that locomotor hyperactivity in this model was inhibited by several selective D 4 antagonists as by the stimulant methylphenidate, but not antagonists that bind preferentially to the D 2 or 5-HT 2A receptor Zhang et al, 2001Zhang et al, , 2002. Given a hypothesized role of working memory deficits in ADHD (Pennington and Ozonoff, 1996;Denney and Rapport, 2001), beneficial effects of L-745,870 on cognition identified in the current study encourage further consideration of D 4 antagonists as novel treatments for clinical ADHD and other disorders of attention and cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Using young rats with neonatal 6-hydroxydopamine lesions as a model for ADHD, we reported that locomotor hyperactivity in this model was inhibited by several selective D 4 antagonists as by the stimulant methylphenidate, but not antagonists that bind preferentially to the D 2 or 5-HT 2A receptor Zhang et al, 2001Zhang et al, , 2002. Given a hypothesized role of working memory deficits in ADHD (Pennington and Ozonoff, 1996;Denney and Rapport, 2001), beneficial effects of L-745,870 on cognition identified in the current study encourage further consideration of D 4 antagonists as novel treatments for clinical ADHD and other disorders of attention and cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral inhibition has been operationalized using a variety of measures, including the Continuous Performance Task (CPT) (see, for reviews, Barkley et al, 1992;Corkum & Siegel, 1993;Losier et al, 1996), delay of gratification tasks (DGTs) (Campbell, Douglas, & Morgernstern, 1971;Pennington & Ozonoff, 1996;Weyandt & Grant, 1994), and the Stroop Test (see for review, Homack & Riccio, 2004). Consistent with this literature, in the current study, behavioral inhibition is measured using CPT commission errors, DGT waiting time, and Stroop interference effects.…”
Section: Studies Of Inhibition and Adhd Symptoms In Childrenmentioning
confidence: 90%
“…The emphasis on executive function deficits, such as deficient behavioral inhibition, in models of ADHD has progressed in tandem with empirical research exploring their interrelation (Barkley, 1997;Nigg, 2001;Pennington & Ozonoff, 1996). To date, the overwhelming majority of studies assessing various aspects of inhibition have demonstrated a concurrent inhibition deficit in school-aged children exhibiting ADHD symptoms compared with children without signs of ADHD (see, for reviews, Barkley, Grodzinsky, & DuPaul, 1992;Corkum & Siegel, 1993;Homack & Riccio, 2004;Losier, McGrath, & Klein, 1996;Oosterlaan, Logan, & Sergeant, 1998;Pennington & Ozonoff, 1996;Tannock, 1998).…”
Section: Studies Of Inhibition and Adhd Symptoms In Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, EF appears to be a core deficit in both populations. It should be noted, however, that some research suggests that EF impairment in ADHD may be associated only with response inhibition and not setshifting dimensions (Bennetto & Pennington, 2003;Pennington & Ozonoff, 1996), and some studies find inconsistent or no significant neuropsychological deficits for ADHD on EF measures (Geurts et al, 2005).…”
Section: Introductionmentioning
confidence: 99%